Food Resources in Forests and Grasslands of China: Potentials and Realization Paths - Xiaokun Tian; Xibing Jiang; Hongjun Wu; Yangdong Wang (中国工程科学)
Food security is of paramount importance to a country. Therefore, it is vital to develop food resources in an all-round and multi-channel way to satisfy people's diversified food-consumption needs. It is necessary to stick to an all-encompassing approach to food and fully develop food resources in forests and grasslands, thereby supporting the historic transformation from "having enough to eat" to "eating well". This study summarizes the general situation and industrial development status of food resources in forests and grasslands of China, analyzes the development potentials of these food resources, and proposes paths for realizing the potentials. It is suggested to strengthen the top-level design to create a national food resource layout system while sticking to an all-encompassing approach to food. Basic research and applied technology development should be consistently conducted to support the scientific and technological innovation in the whole industry chain of food resources in forests and grasslands. Additionally, it is necessary to build a market- and consumer-demand-oriented mechanism for the development and utilization of food resources in forests and grasslands, and improve the safeguard measures for the high-quality development of the forest and grassland food industry, so as to store the grain productivity in forests and grasslands and make positive contributions in ensuring China's food security, providing multiple food supplies, and promoting rural revitalization.